Modeling of 2-DOF Hexapod Leg Using Analytical Method - Wajiansyah, Agusma; Supriadi, Supriadi; Gaffar, Achmad Fanany Onnilita; Putra, Arief Bramanto Wicaksono (Universitas Muhammadiyah Yogyakarta, 2021)
Walking robot is one type of mobile platform that has locomotion type